2015
DOI: 10.1155/2015/135787
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Subthreshold Resonant Properties in Pyloric Dilator Neurons

Abstract: Various types of neurons exhibit subthreshold resonance oscillation (preferred frequency response) to fluctuating sinusoidal input currents. This phenomenon is well known to influence the synaptic plasticity and frequency of neural network oscillation. This study evaluates the resonant properties of pacemaker pyloric dilator (PD) neurons in the central pattern generator network through mathematical modeling. From the pharmacological point of view, calcium currents cannot be blocked in PD neurons without removi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Compared with many experimental and simulation results (Zemankovics et al, 2010 ; Gastrein et al, 2011 ; Pavlov et al, 2011 ) of the subthreshold resonance and precise spike-timing induced by I h , there are much less theoretical investigations (Rotstein, 2015 ; Vazifehkhah et al, 2015 ) to explain the corresponding dynamical mechanism. It is well known that neuron is a nonlinear dynamical system which can be described by the differential equations, and bifurcation analysis has been identified as an effective method to identify the dynamical mechanism of the electrophysiological properties of neurons.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with many experimental and simulation results (Zemankovics et al, 2010 ; Gastrein et al, 2011 ; Pavlov et al, 2011 ) of the subthreshold resonance and precise spike-timing induced by I h , there are much less theoretical investigations (Rotstein, 2015 ; Vazifehkhah et al, 2015 ) to explain the corresponding dynamical mechanism. It is well known that neuron is a nonlinear dynamical system which can be described by the differential equations, and bifurcation analysis has been identified as an effective method to identify the dynamical mechanism of the electrophysiological properties of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the experimental studies found that I h can induce subthreshold membrane resonance and enhance spike-timing precision characterized by the standard deviation ( STD ) or coefficient variation ( CV ) of the interspike intervals (ISIs) (Zemankovics et al, 2010 ; Gastrein et al, 2011 ; Pavlov et al, 2011 ; Borel et al, 2013 ; Gonzalez et al, 2015 ). Resonance means that impedance profile of a neuron to external stimulus reaches a maximal value at a certain value corresponding to an intrinsic frequency preference (Rotstein, 2015 ; Vazifehkhah et al, 2015 ), which is an important factor related to the rhythmic oscillations (Gasparini and DiFrancesco, 1997 ; Hutcheon and Yarom, 2000 ; Giocomo et al, 2007 ; Moca et al, 2014 ; Gonzalez et al, 2015 ). For example, hippocampal pyramidal neurons (Hu et al, 2002 ; Zemankovics et al, 2010 ; Gastrein et al, 2011 ; Borel et al, 2013 ) exhibit subthreshold resonance to the injection of sinusoidal current, and their resonant properties contribute to the emergence of Theta oscillations (Zemankovics et al, 2010 ; Stark et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 A1 shows the circuit model to simulate voltage waveforms in response to electrical stimulation delivered by small‐distance stimulation electrodes. In this circuit model, motoneurons are represented by RLC (resistor, inductor, and capacitor) components (green blocks P1–P4 in Figure A1). Muscle fibers are represented by RC (resistor and capacitor) components (blue blocks in Figure A1).…”
Section: Resultsmentioning
confidence: 99%